AI and IoT-based intelligent automation in robotics - Dubey, Ashutosh Kumar (John Wiley & Sons, Inc. ; Scrivener Publishing, 2021)
"Artificial Intelligence (AI) is one of the trending technologies in the recent era. The emergence of the robotics and application of AI in it brings out a significant change in the domain. Various algorithms that emerge in AI and the computational efficiency of the systems has made it possible to address a number of applications through robotics. The Internet of Things (IoT) is the important domain that plays a major role in robotics. With the aid of IoT and AI, robotics is an exponential development in providing solutions to complex technical problems. The 24 chapters in this book provides a deep overview of robotics and the application of AI and IoT in robotics. It contains the exploration of AI and IoT based intelligent automation in robotics. The various algorithms and frameworks for robotics based on AI and IoT are presented, analyzed, and discussed. This book also provides insights on application of robotics in education, healthcare, defense and many other fields which utilize IoT and AI. It also introduces the idea of smart cities using robotics"--